Effective methods for modern healthcare service quality and evaluation - Manolitzas, Panagiotis; Grigoroudis, Evangelos; Matsatsinis, Nikolaos F.; Yannacopoulos, Denis, 1949- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2016)
"This book is a reference source for the latest research on emerging tools and methodologies for the design of healthcare models, providing expert analyses on trouble-shooting specific problems in the industry and creating optimal hospital environments"--